The impact of a virtual wound on pain sensitivity: insights into the affective dimension of pain - Ingrid Koopmans; Ingrid Koopmans; Robert-Jan Doll; Robert-Jan Doll; Maurice Hagemeijer; Robert van Barneveld; Marieke de Kam; Geert Jan Groeneveld; Geert Jan Groeneveld (Frontiers in Pain Research)
BackgroundThe perception of pain is difficult to assess due to the complex combination of various components related to nociception, experience, and cognition. There are currently no biomarkers to assess the affective component of pain in healthy volunteers. Using Virtual Reality (VR), it may be possible to assess changes in pain perception when adding an affective component to painful stimulation.MethodsIn this two-visit feasibility study, we assess the effect of a simulated wound in VR on the electrical pain detection (PDT) and tolerance (PTT) threshold in 24 healthy male study participants. The VR simulation presented a copy of the research room from first person view. Prior to each VR assessment, study participants were primed by interacting with the VR environment. Two conditions were assessed: (1) VR-Wound: a burn-wound, smoke, and electrical sparks become visible and audible with increasing stimulus intensity, and (2) VR-neutral: no additional aspects. The PDT and PTT to electrical stimuli were recorded during both VR conditions and outside of VR. VAS-Questionnaires were used to assess unpleasantness and fear.ResultsThe PDT decreased when a virtual wound is presented compared to a neutral condition. Study participants experienced the electrical stimulation as more painful and more intense during the wound simulation than during the neutral condition. The effect was more pronounced during the second visit.ConclusionVR enhanced the perception of pain, thereby providing new insights into the affective component of pain. Further testing of this methodology is warranted by performing a clinical study that evaluates drug effects on the affective component of pain.